Effect of reduced gravity and weightlessness on vapor bubble dynamics and heat transfer in boiling liquid - Rusanov, K. V.; Shcherbakova, N. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The results on boiling of liquids and gas bubbling under simulated long-term reduced gravity are reported. The possibility of extrapolating these results to the real spacecraft conditions is considered and the program of on-board space experiments is proposed to test the current theory at the relative accelerations 10-4 -10 -6 which are unattainable in a laboratory. Tests in free-fall towers, in aircraft, or in ballistic rockets are inadequate since only prolonged (over one hour) experiments in the Earth`s orbit can provide reliable data. The advantage of cryogenic liquids, helium, in particular, in space experiments is discussed.